Karakteristik Rumah Tangga Miskin Mustahik Program Bantuan Rumah oleh Baitul Mal Kota Banda Aceh - Renaldi, Didi; Manaf, Asnawi (Faculty of Social Science, Universitas Negeri Semarang, 2019)
Everyone has the right to live and fulfillment of housing needs will provide a safe and comfortable feeling for every Indonesian citizen to build a family and prepare future generations for a better life. The limited access of the poor to the housing finance system plus the low efficiency of limited housing finance and the pattern of subsidies that allow the wrong target to occur. The local government agency, Baitul Mal Kota Banda Aceh has a program to build and rehabilitate homes for the poor. With the large number of funds collected from Zakah, Infaq, and Shadaqah (ZIS) in Banda Aceh City being a question mark on the number of decreases in the number of poor people in Banda Aceh. The purpose of this study was to find out the demographic, social and economic characteristics of recipients of housing assistance located in Banda Aceh City. The analytical method used is quantitative descriptive with purposive sampling of 29 recipients of permanent home assistance and renovation. The results of the research show that the community groups that get the most benefit are the poor with the middle poverty level.Ã‚Â